Analisa Sistem Informasi Akuntansi Pada Penjualan E-Commerce “Jims Honey” Selama Pandemi COVID-19 - Taufiq, Ahmad; Nas’ifah, Zanitsa; Supriadi, Iman (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2021)
E-commerce is a digital-based electronic buying and selling system that is easily accessible anywhere, anytime and by anyone. With the current condition of the COVID-19 pandemic, where health protocols are very stressed, many people use e-commerce to meet their needs without having to meet face to face. Jims Honey Gedangan uses this e-commerce system to expand its sales distribution. For sales reports, Jims Honey Gedangan makes an analysis obtained from the use of the Sales Accounting Information System which is then applied to e-commerce as an effort to make sales reports easier. Sellers can supervise their sales by making a recapitulation of the information obtained from the Sales Accounting Information System in e-commerce. In the future, the use of e-commerce systems and the application of the Sales Accounting Information System are expected to be widely used by MSME entrepreneurs to help increase sales and control the turnover of their products during a pandemic.